Years of renewal - Kissinger, Henry ([S.l.] : Simon & Schuster, Inc., 1999)
The third & final volume of the memoirs of former Sec. of State Henry Kissinger. Begins with the resignation of Nixon -- including Kissinger's assessment of Nixon's tortured personality & the self-inflicted tragedy that ended his presidency & made Kissinger, for a time, the most powerful man in American government. Then takes the reader through the years of Ford's administration, in which Kissinger continued to play a decisive role. Details the agony of the final U.S. extrication from Vietnam & takes us inside the White House to show our leaders in a time of crisis. He recounts the many major decisions & crises that he had to deal with. He provides intimate & candid portraits of world leaders, from Mao Zedong to Leonid Brezhnev.